Seasonal variations of NOM composition and their reactivity in a low humic water. Issue 3 (8th October 2013) - Karapinar, Nazan; Uyak, Vedat; Soylu, Senay; Topal, Tufan
<x xml:space="preserve">Abstract</x> Natural organic matter (NOM) and its potential to form disinfection by‐products (DBPs) during water treatment are of great public health concern. Understanding the seasonal changes in NOM composition and their reactivity in DBP formation could lead to a better treatment of drinking water and a more consistent water quality. NOM from the Terkos Lake was fractionated and characterized by XAD resin adsorption and ultrafiltration (UF) techniques during four different seasons within a year. XAD fraction analysis indicates that the HPI (38%) and the TPI (21%) were the dominant chemical fractions as DOC masses across the sampling period. Moreover, the fractions contributing to the most UV254 absorbance were HPO, which accounted for more than 72% of total UV254. It was found that the percentages of UV254 of HPI and TPI showed significant amount of variation with coefficients of variation of 48% (HPI) and 35% (TPI), respectively. Moreover, it was concluded that the HPO fraction was the primary THM precursor, which contributed more than 48%, and while the primary fraction of HAA precursors was found to be TPI, accounting for more than 47% of total HAAFP with exceptions in January 2011. As obviously seen in this study, the hydrophobic constituents in Terkos Lake water are on the low end of the spectrum in terms of their reactivity to form HAAs. In the context of THM reactivity, the physical properties (i.e., moleculer size) of Terkos Lake NOM are more important than their chemical properties (i.e., aromaticity). On the other hand, the predominant fraction as the source of HAAs precursors was found to be with the TPI and HPI chemical fractions. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 962–971, 2014